Multidimensional Scale of Perceived Social Support (MSPSS): Psychometric Properties in Peruvian Universities - Nicho Almonacid , Tracy Lucyana (2023)
The purpose of this instrumental design study was to analyze the psychometric evidence of the Multidimensional Scale of Perceived Social Support (MSPSS) for its application in university students in Metropolitan Lima. A total of 520 students participated, 292 women (56%) and 228 men (44%), between 18 and 61 years of age (M = 24.89, SD = 5.17). The confirmatory factor analysis showed acceptable values for the bifactor model: χ2/gl = 4.645, CFI = .99, TLI = .98, SRMR = .027, RMSEA = .084 (90% C.I., .072, .096) and WRMR = .99. Additionally, a value of H = .945, PUC = .727, ECV = .695 and the ωH = .85 were obtained for the general factor. Convergent validity was examined with the General Self-Efficacy Scale (GSES) (r = .50; r2 = .25) and divergent validity with the Test Anxiety Inventory-State (TAI-State) (r = -.32; r2 = .10). In addition, reliability was determined through the ordinal omega coefficient for the general scale (ω = .97) and its three factors respectively: (ω = .90), (ω = .96) and (ω = .93). Finally, the factorial invariance analysis showed evidence of fairness by sex (ΔCFI<.010, ΔRMSEA <.015). In conclusion, the MSPSS has adequate psychometric properties to quantify the variable perceived social support in Lima university students.